2019
DOI: 10.1111/famp.12481
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Immigration‐Related Stress in a Culturally Adapted Parenting Intervention for Mexican‐Origin Immigrants: Initial Positive Effects and Key Areas of Improvement

Abstract: Culturally adapted evidence‐based parenting interventions constitute a key strategy to reduce widespread mental health disparities experienced by Latinx populations throughout the United States. Most recently, the relevance of culturally adapted parenting interventions has become more prominent as vulnerable Latinx populations are exposed to considerable contextual stressors resulting from an increasingly anti‐immigration climate in the country. The current study was embedded within a larger NIMH‐funded invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Second, mental health support providers need to focus on stress not only from the acculturation process but also from the child-rearing process among immigrant women. Some mental health promotion programs and interventions only focused on cross-cultural stress while ignoring parenting stress among immigrant women [ 12 , 59 ]. Third, since parenting stress could influence the effectiveness of mental health support, more attention needs to focus on parenting stress to ensure the effectiveness of mental health support to avoid wasting social resources.…”
Section: Discussionmentioning
confidence: 99%
“…Second, mental health support providers need to focus on stress not only from the acculturation process but also from the child-rearing process among immigrant women. Some mental health promotion programs and interventions only focused on cross-cultural stress while ignoring parenting stress among immigrant women [ 12 , 59 ]. Third, since parenting stress could influence the effectiveness of mental health support, more attention needs to focus on parenting stress to ensure the effectiveness of mental health support to avoid wasting social resources.…”
Section: Discussionmentioning
confidence: 99%
“…On recruitment strategies, we found that the most often used recruitment strategy reported in the included studies were recruitment from the local immigrant communities and agencies/organisations. Studies reported that direct invitation with a bilingual approach and word-of-mouth invitations were considered effective [28,36,44,62,80,84,89,101,[105][106][107]. Only one study reported using social media for recruitment [98] which could be one potential way to reach participants in the future programmes.…”
Section: Discussionmentioning
confidence: 99%
“…4. Most of the studies were qualitative (n = 20) [26,31,39,42,49,57,68,[70][71][72][73][74][75][76][77][78][79][80][81][82] and RCT studies (n = 18) [ 23,34,36,38,44,58,64,[83][84][85][86][87][88][89][90][91][92][93]. A total of 14 of the studies lacked a clear methods section or the methods were inadequately reported [27,28,30,32,33,45,55,56,59,66,[94][95]…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations